ISSLS Prize Winner: Vertebral Endplate (Modic) Change is an Independent Risk Factor for Episodes of Severe and Disabling Low Back Pain. Issue 15 (1st August 2015) - Määttä, Juhani H.; Wadge, Sam; MacGregor, Alex; Karppinen, Jaro; Williams, Frances M.K.
Abstract : Study Design: Longitudinal cohort study of twins representative of the general population. Objective: To assess the relationship between Modic change (MC) and severe, disabling low back pain (LBP), features of intervertebral disc degeneration (DD) and incident MC during 10-year follow-up. Summary of Background Data: MC describes vertebral endplate and bone marrow lesions visible on magnetic resonance imaging (MRI). MC has been associated with DD. It remains unclear whether MC causes LBP independently or through association with DD. Moreover, association of MC with severe, disabling LBP is uncertain. Methods: Volunteers were recruited from the TwinsUK register to MRI and interview between 1996 and 2000 with a subset attending for follow-up a decade later. MC, DD (evaluated by loss of disc height and signal intensity, presence of disc bulge and anterior osteophytes) and Schmorl's nodes (SN) were determined on T2-weighted lumbar MR scans. Results: Complete data were available for 823 subjects at baseline and 429 at follow-up. Mean age at baseline was 54.0 years (range 32–70) with 96% females. The prevalence of MC was 32.2% at baseline and 48.7% at follow-up. Subjects with MC were older ( P < 0.001) and more overweight (BMI: P = 0.026, weight: P < 0.001). At both baseline and follow-up, more subjects reporting severe LBP demonstrated MC (subjects with MC vs . without MC: 35.0% vs . 16.4% respectively, P < 0.001 at baseline; and 35.1% vs . 20.0% respectively, P < 0.001 at follow-up). In multivariable analyses, MC remained significantly associated with episodes of severe, disabling LBP (OR 1.58; 95% CI 1.04–2.41) after adjustment for age, BMI, DD, and SN at baseline. Loss of disc height and disc signal intensity were independently associated with prevalent MC at baseline, and disc height and disc bulge with incident MC during follow-up. Conclusion: MC is an independent risk factor for episodes of severe and disabling LBP in middle-aged women. These observations support further work aimed at identifying the precise histology underlying MC. Level of Evidence: 2 Abstract : Modic change was associated with episodes of severe, disabling LBP independently of age, BMI, disc degeneration and SN. Our results showed that loss of disc height and signal intensity were associated with prevalent Modic change, whereas disc narrowing and bulge were risk factors of incident Modic change during 10-year follow-up.